2023
DOI: 10.1097/rlu.0000000000004505
|View full text |Cite
|
Sign up to set email alerts
|

First Clinical Experience With [68Ga]Ga-FAPI-46-PET/CT Versus [18F]F-FDG PET/CT for Nodal Staging in Cervical Cancer

Abstract: Conflicts of interest and sources of funding: The authors have no conflicts of interest to declare. This study has been supported by SOFIE by the provision of precursors for FAPI synthesis. A.D. discloses research support from Siemens Healthineers, Life Molecular Imaging, GE Healthcare, AVID Radiopharmaceuticals, SOFIE and Eisai; Speaker Honorary and/or Advisory Boards fees from Siemens Healthineers, Sanofi, GE Healthcare, Biogen, Novo Nordisk; Invicro Stock from Siemens Healthineers, Lantheus Holding, and a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…However, [ 68 Ga]Ga-FAPI-04 has a relatively short tumor retention, making it unsuitable for theranostic purposes. Therefore, many other promising FAP-targeted radioligands are being developed and some are being evaluated clinically, such as [ 177 Lu]Lu-FAP-2286 [ 25 ] and [ 68 Ga]Ga-FAPI-46 ( Figure 1 ) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, [ 68 Ga]Ga-FAPI-04 has a relatively short tumor retention, making it unsuitable for theranostic purposes. Therefore, many other promising FAP-targeted radioligands are being developed and some are being evaluated clinically, such as [ 177 Lu]Lu-FAP-2286 [ 25 ] and [ 68 Ga]Ga-FAPI-46 ( Figure 1 ) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, 18 F-FDG uptake decreases in luminal A and invasive lobular carcinoma, causing false-negative results in the assessment of disease stage 4,5 . 68 Ga-FAPI PET/CT has recently emerged as a potential imaging modality, which could have a role in different clinical situations, including BC 6–11 . Kömek et al 12 demonstrated the superiority of 68 Ga-FAPI-04 PET/CT over 18 F-FDG PET/CT in predominantly ER + primary tumors and in detecting LNs and distant metastases.…”
mentioning
confidence: 99%
“…4,5 68 Ga-FAPI PET/CT has recently emerged as a potential imaging modality, which could have a role in different clinical situations, including BC. [6][7][8][9][10][11] Kömek et al 12 demonstrated the superiority of 68 Ga-FAPI-04 PET/CT over 18 F-FDG PET/CT in predominantly ER + primary tumors and in detecting LNs and distant metastases. In contrast to them, Ding et al 13 revealed that the sensitivity of 68 Ga-FAPI-04 PET/CT decreased at the advanced stage of BC.…”
mentioning
confidence: 99%
“…Ga-FAPI PET/CT showed potential in the detection of tumors. [1][2][3][4] However, false-positive uptake of FAPI has been reported in nonmalignant lesions, 5,6 including cryptococcosis and tuberculosis. 7,8 This case re-emphasizes that pulmonary cryptococcosis manifests as increased FAPI uptake.…”
mentioning
confidence: 99%
“…However, the histopathologic result revealed the diagnosis of pulmonary cryptococcosis ( E ) and hepatic adenocarcinoma ( F ). Many previous studies have reported that 68 Ga-FAPI PET/CT showed potential in the detection of tumors 1–4 . However, false-positive uptake of FAPI has been reported in nonmalignant lesions, 5,6 including cryptococcosis and tuberculosis 7,8 .…”
mentioning
confidence: 99%